(untitled) (Research, Society and Development, 2021)
The current COVID-19 pandemic caused by the new SARSCoV-2 coronavirus, spread rapidly and resulted in numerous fatal cases. Coagulopathy is one of the main complications of this disease, and it can occur in any patient infected by the virus; one of the risk groups, obstetric patients, requires more attention, due to coagulative and hemostatic changes expected in this group. The purpose of the review was to conduct a literature review of articles that address the relationship between hypercoagulopathy and pregnant women infected by the SARS-COV-2 virus. The search was performed in Google Scholar, Virtual Health Library (BVS), Scientific Electronic Library Online (Scielo) and PubMed databases. The following descriptors were used “pregnant women”, “coagulopathy”, “blood disease”, “COVID-19”, “haematological alterations”. Bleeding disorders occur in patients who are pregnant or not infected by the SARS-COV-2. Pregnant women are a group more susceptible to aggravations, due to the hypercoagulability process that already occurs naturally in the gestational period. More studies are needed to show this association, in order to provide adequate care for such patients.